(3MGTjI Ydi TQM GdTeSjIs - (3GdjROj, YHO Gddg Hf GdMSjf Hf YHO Gddg, J (B1015 (3g`s ((3ejQ MSjf Hf Ydj GdMSjfjs)
(3ChdgG (B:s
... (3GdeWdhH HNdGa GdKGfj aEf GdOdGdI Ydi eG jhUd Gdi GdeWdhH dG jdRe Cf jchf ehUdg Edi eG jhUd acja jhUd Edi GdeWdhH hGdChdi efbhV Hbhdg JYGdi (B{ (3hCeG KehO agOjfGgf (B..s
(3BNQgG (B:s
.. (3ef CTHg HebGUO Gdfaj efg HebOeGJg hdPG fQi (B... (3hchfg CTHg HGdebUhO (B.. (3Ydi GdbUO ef GdYde GdYedj MUd WGdHg LYdce Gddg ef GdQGSNjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\80s
(3gOjI GdYGQajf (B1\474s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs